DEVELOPMENT OF SCHOOL WEBSITE AS A MEANS OF PUBLICATION AT KINDERGARTEN DHARMA WANITA 06 MALANG CITY - Naila Sabrina Putri; Yudithia Dian Putra; Munaisra Tri Tirtaningsih (Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to develop a school website as a means of publication at Dharma Wanita 06 Kindergarten in Malang City. The background of this study is the lack of integrated digital publication media, so that the delivery of school information is still limited to WhatsApp group and conventional media. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The website product was validated by subject matter experts, media experts, and users consisting of the school principal and teachers. The validation results showed that the website obtained a feasibility score of 89.17% from subject matter experts, 97.5% from media experts, and 97.66% from users, all of which were in the highly feasible category. Thus, the developed school website was declared feasible for use as a school publication medium.